2004
DOI: 10.1142/s0218495804000063
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Intensive Entrepreneurship in a Social Capital Perspective

Abstract: In 1989 Mitton suggested that success for start-ups not only depends on who you are but also on whom you know. To study the importance of social capital and networks in relation to entrepreneurial activities, research in a Danish start-up context in two knowledge-intensive sectors has been carried out. The research methodology was based on a triangulation approach including a general questionnaire-based survey conducted through the Internet combined with a 85 in-depth interviews in purposefully sampled venture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 18 publications
1
26
1
9
Order By: Relevance
“…After Jacobs, the theory has been used to examine the development of human capital (Coleman 1988), and is being increasingly surfaced in the entrepreneurship field, for example, intensive knowledge (Neergaard & Madsen 2004), venture creation (Liao & Welsch 2005), family business (De Freyman et al 2005;McKeever et al 2005). Coleman (1988) defines social capital by its function.…”
Section: Social Capitalmentioning
confidence: 99%
“…After Jacobs, the theory has been used to examine the development of human capital (Coleman 1988), and is being increasingly surfaced in the entrepreneurship field, for example, intensive knowledge (Neergaard & Madsen 2004), venture creation (Liao & Welsch 2005), family business (De Freyman et al 2005;McKeever et al 2005). Coleman (1988) defines social capital by its function.…”
Section: Social Capitalmentioning
confidence: 99%
“…Research focusing on measuring network interaction in terms of frequency, intensity, and durability has revealed that extensive networks are important to the growth of entrepreneurial ventures because they provide access to resources held by other actors within the network (Shaw and Conway, 2000;Neergaard and Madsen, 2004;Shaw, 2006).…”
Section: Relationship Strength Of Entrepreneurial Networkmentioning
confidence: 99%
“…Les investisseurs sont d'ailleurs soucieux de la bonne entente au sein d'une équipe d'entrepreneurs au-delà du partage des ressources ou compétences. Ainsi que l'indiquent Neergaard et Madsen (2004) Il sera alors intéressant de cerner dans quelle mesure les équipes observées s'inscrivent dans un contexte de liens forts ou de liens faibles.…”
Section: L'équipe Une Logique De Réseaux Sociauxunclassified
“…Cependant, le type d'entreprises étudiées ne possédant pas les caractéristiques des gazelles ou autres entreprises fortement innovantes n'est pas de nature à retenir l'attention de venture capitalists ou autres business angels. Cet aspect est de nature à orienter les résultats obtenus, les études conduites, par ailleurs, ayant montré que les créations en équipe sont plus fréquentes dans le domaine des technologies (Moreau, 2006 ;Neergaard et Madsen, 2004 ;Bernasconi, 2000). Cependant, nous avons observé une majorité d'équipes dans nos cas d'entrepreneurs ordinaires.…”
Section: Limitesunclassified